Meningkatkan Hasil Belajar Siswa Melalui Penerapan Pembelajaran Kooperatif Student Active Learning Kelas III SDK Wanno Baru pada Tema 2 Subtema 1. - Melkianus Ama Kii; Daindo Milla; Dominggus Lero Bili; Petrus Lende (Mataram University, 2026)
This study aims to improve students’ learning outcomes through the implementation of the Cooperative Student Active Learning (SAL) model on Theme 2, “Loving Plants and Animals,” in Grade III at SDK Wanno Baru. The research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The research subjects were 20 students (10 males and 10 females). Data collection methods included tests, observations, and documentation. The research instruments consisted of observation sheets for teacher and student activities, as well as learning outcome tests. The results showed an improvement in students’ learning outcomes: in Cycle I, only 8 students achieved mastery (40%), which increased in Cycle II to 16 students achieving mastery (80%). Thus, it can be concluded that the implementation of the Student Active Learning model is effective in improving students’ learning outcomes on the theme “Loving Plants and Animals.”